19F NMR‐Based Fragment Screening for 14 Different Biologically Active RNAs and 10 DNA and Protein Counter‐Screens. (25th September 2020) - Binas, Oliver; de Jesus, Vanessa; Landgraf, Tom; Völklein, Albrecht Eduard; Martins, Jason; Hymon, Daniel; Kaur Bains, Jasleen; Berg, Hannes; Biedenbänder, Thomas; Fürtig, Boris; Lakshmi Gande, Santosh; Niesteruk, Anna; et al.
Abstract: We report here the nuclear magnetic resonance 19 F screening of 14 RNA targets with different secondary and tertiary structure to systematically assess the druggability of RNAs. Our RNA targets include representative bacterial riboswitches that naturally bind with nanomolar affinity and high specificity to cellular metabolites of low molecular weight. Based on counter‐screens against five DNAs and five proteins, we can show that RNA can be specifically targeted. To demonstrate the quality of the initial fragment library that has been designed for easy follow‐up chemistry, we further show how to increase binding affinity from an initial fragment hit by chemistry that links the identified fragment to the intercalator acridine. Thus, we achieve low‐micromolar binding affinity without losing binding specificity between two different terminator structures. Abstract : Checking out RNA druggability by NMR : Fourteen RNAs have been screened and ten DNA and proteins were counter‐screened to show that fragment libraries can differentiate between different RNA targets with up to 15‐fold selectivity.